ASPIRASI KELUARGA PETANI MENYEKOLAHKAN ANAK KE SEKOLAH KEJURUAN DI DESA BUNTALO KABUPATEN BOLAANG MANGONDOW - Windy Evanjel Runtuwene; Ferdinand Kerebungu; Zoni Singal (Labor Program Studi Pendidikan Sosiologi, 2021)
The problem in this study is that Buntalo Village is a village located in Lolak sub-district, where most of the people are in low economic conditions, although there are also people who have good economic conditions. Buntalo village people who have a mediocre income or family economy are farmers who work in the fields where their income depends on the availability of jobs from the owners of the fields. With mediocre economic income, it also has an impact on children's education, where the education of children in Buntalo village is not at a good level of education, where the education level in Buntalo village is only up to elementary and junior high school levels. The research method used in this research is qualitative research. The level of income is one measure to see the level of community welfare. Especially for lowland rice farmers with narrow lands, whose access to land owned is very limited. However, it does not mean that they belong to the poor group because they have other accesses (education, labor) and can be utilized.